Faktor-faktor yang mempengaruhi tingkat kemiskinan di provinsi kalimantan timur - Rizky Permana (FORUM EKONOMI, 2016)
The purpose of this research is to determine interrelatedness between  economic growth and income distribution in Berau regencies. Hypothesis positive interrelatedness linkages economic growth and income distribution in Berau regencies. The analytical tool used in this research is by correlation test. Based on the analysis by calculating the Pearson product moment correlation is positive but not significant between the distribution of low income and moderate in economic growth as well as the correlation is negative and significant correlation between income distribution of high economic growth, while based on the results of the calculation of Spearman Rank correlation There is a positive correlation and not significant correlation between economic growth and income distribution.Keywords: Economic Growth, Income Distribution